Sensitivitas dan Spesifisitas Nested Polymerase Chain Reaction untuk Mendeteksi DNA Coxiella burnetii (SENSITIVITY AND SPECIFICITY OF NESTED POLYMERASE CHAIN REACTION FOR DETECTION OF COXIELLA BURNETII DNA) - Purnawarman, Trioso; Wibawan, I Wayan Teguh; Pasaribu, Fachriyan Hasmi; Setiyono, Agus; Saepulloh, Muharam (Jurnal Veteriner, 2012)
Sensitivity and specificity of nested polymerase chain reaction (nested PCR) to detect Coxiella burnetii(C. burnetii) DNA were studied. The primer system which consists of external primers (OMP1 and OMP2)and internal primers (OMP3 and OMP4), was designed from the nucleotide sequence of the com I geneencoding for 27 kDa outer membrane protein and used to specifically amplify a 501 bp and 438 bp fragment.This nested PCR assay was 50 fold more sensitive than that of using PCR external primer only. TheNested PCR has a detection limit as low as 300 pg/?l. Specificity studies showed that nested PCR onlydetected C. burnetii DNA and did not happened Brucella abortus, Escherichia coli, Pseudomonas aeruginosaand Campylobacter Jejuni DNA. Nested PCR has high senstively and specificaly diagnostic method of C.burnetii as agent of Q fever disease.
Keywords: nested PCR, Coxiella burnetii, sensitivity and specificity